2020
DOI: 10.1007/s10654-020-00710-8
|View full text |Cite
|
Sign up to set email alerts
|

Calcium intake, calcium supplementation and cardiovascular disease and mortality in the British population: EPIC-norfolk prospective cohort study and meta-analysis

Abstract: The role of dietary calcium in cardiovascular disease prevention is unclear. We aimed to determine the association between calcium intake and incident cardiovascular disease and mortality. Data were extracted from the European Prospective Investigation of Cancer, Norfolk (EPIC-Norfolk). Multivariable Cox regressions analysed associations between calcium intake (dietary and supplemental) and cardiovascular disease (myocardial infarction, stroke, heart failure, aortic stenosis, peripheral vascular disease) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…In contrast, the findings from the British population, 6 the older Chinese community‐dwelling population 7 or the US population, 9 discovered that higher calcium intake was associated with decreased mortality rate. We at first attributed the contradictory results to different forms of calcium intake, but in studies taken forms of calcium intake into consideration, some found higher dietary calcium intake was not associated with premature death, 8,9,12 while others found a statistically significant relationship with lower mortality risk 6,7,10,11 . Thus we assumed that certain characteristics of the different populations may confound the association, so herein we carried out analyses in people with hypertension from NHANES based on previous physiological evidence 13–17 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, the findings from the British population, 6 the older Chinese community‐dwelling population 7 or the US population, 9 discovered that higher calcium intake was associated with decreased mortality rate. We at first attributed the contradictory results to different forms of calcium intake, but in studies taken forms of calcium intake into consideration, some found higher dietary calcium intake was not associated with premature death, 8,9,12 while others found a statistically significant relationship with lower mortality risk 6,7,10,11 . Thus we assumed that certain characteristics of the different populations may confound the association, so herein we carried out analyses in people with hypertension from NHANES based on previous physiological evidence 13–17 .…”
Section: Discussionmentioning
confidence: 97%
“…8,12 These controversial findings may in part due to different forms of calcium intake (dietary calcium or calcium supplements) 8,12 and different populations the researchers based on. [6][7][8][9] The role of calcium in the development of hypertension and CVD like arteriosclerosis has been recognized [13][14][15][16][17] ; meanwhile, individuals with hypertension have lower calcium intake than the general population. 18 We therefore assume that calcium in the hypertensive population may have a unique effect on health compared with those without hypertension, and heterogeneity of previous studies on the association between calcium intake and mortality may be attributed to hypertension morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, high calcium intake is suggested to be correlated with a decreased risk of incident atherosclerosis [ 31 ]. There is evidence suggesting that higher calcium intake is associated with better lipid profiles and lower blood pressure [ 32 , 33 ], which may be beneficial for cardiovascular health [ 34 ]. According to the above findings, we speculated that high dietary calcium might have an important role in improving microvascular change in patients with diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Our current findings demonstrated that lower calcium levels were associated with higher risk of mortality among community-dwelling older adults. Previously, several cohort studies and meta-analyses have demonstrated that dietary calcium intake was inversely associated with the risk of all-cause mortality [ 30 , 31 , 32 ]. Meanwhile, lower serum calcium levels (<7.9 mg/dL) during admission were associated with higher risk of in-hospital mortality among the hospitalized patients [ 33 ].…”
Section: Discussionmentioning
confidence: 99%